관광객 요구분석에 따른 복합자연공원 개발방향 연구 - 조의영(Ui-Young Cho) (한국콘텐츠학회 논문지, 6(11), 2006)
This study was conducted to suggest new development model for national & public parks by applying fascinating theme to the existing standardized development of those park. For this purpose, YeonIn Mountain Provincial Park was chosen as object of this research, which is located in GaPyeong, Kyonggi Province. The results from analysis of demand for tourism trend and development were as follows. Most of visitors(87%) come from the metropolitan area and their age are between the ages of 20 and 30. And the visitors' preference for accommodation is the independent villa style. For commercial facility, the strong expansion for food and beverage facilities and stores was needed. The future facilities and activities which they want to experience and e are health-recreation facility and ecological experience based on nature. From these results, It might conclude that we have to develop the qualified nature park with various theme focused on experience and recreation, and that we do preserve the environment. 본 연구의 목적은 보전 중심의 획일적인 국공립공원 개발방식에서 벗어나 보전개념과 함께 흥미 있는 테마를 적용하여 복합적인 개념의 자연공원 개발방안을 제시하는 것이다. 관광트랜드와 개발에 대한 요구분석 결과 대상지인 경기도 가평 연인산 도립공원의 방문객 대다수가 수도권에 거주(87%)했고, 주 이용객은 20-30대(52%)로 나타났다. 숙박시설은 독립빌라형을 가장 선호(47%)했고, 상업시설은 식음 및 판매시설에 대한 확충(65%)을 가장 우선적으로 요구하는 것으로 조사되었다. 향후 도입시설에 있어 자연생태체험(43%), 건강 휴양시설(34%)을 선호하는 것으로 나타났다. 실증분석 결과, 체험과 휴양을 핵심 컨셉으로 한 다양하고 질 높은 테마형 자연공원조성이 필요하고 환경보전을 병행해야 하겠다.